Investigation of Performance On Low and High Temperature Nitrided 316L Austenitic Stainless Steel On Impact Test and Scratch Test - Ismail, Siti Syahirah (IRC, 2016)
Austenitic stainless steel 316L is exposed to gas nitriding at 400 °C, 600 °C, and 1100 °C with fixed pressure and eight (8) hours exposure time. The properties on the surface and the toughness of samples have been improved significantly when the nitriding process is done. This is resulting the hardness is increased up to 970.4 HV. The surface roughness and scratch test of each temperature tested are also increased. Meanwhile, the impact energy absorbed is increased up to 135.7 J which is almost double from unnitrided sample. The microstructure of the samples is identified under scanning electron microscope after being tested